Integrated framework for hydrologic modelling in data-sparse watersheds and climate change impact on projected green and blue water sustainability - Lawal, I. M.; Bertram, D.; White, C. J.; Jagaba, A. H. (Frontiers in Environmental Science, 2023)
Climate and hydrologic hazards threaten the distribution of watersheds' water resources in time and space, necessitating planning for sustainable resilience and adaptation. Hydrologic modelling has emerged as a potential solution for understanding watershed responses to projected climate change and a prediction model that can deliver actionable information is necessary, although it requires basin-scale observations to calibrate the model to reliably predict basin-scale water resources hazards. Such luxury is not always tenable in watersheds with inadequate ground-based observation. However, satellite-based ET data coupled with a machine learning feature selection as a data refinement process has made integrated water balance modelling widely regarded alternative for improving the capability of watershed modelling processes in data-sparse regions. This study developed a convincing hydrologic model framework to calibrate sufficiently and provide accurate behavioural solutions for model responses. The framework was applied to four subbasins that form the larger Lake Chad basin. The model results were applied to assess the dynamic changes in projected blue and green water resource sustainability in response to climate change in one of the subbasins. Study findings indicate that hydrologic fluxes can be simulated accurately with varying degrees of acceptability with R 2 and NSE values in the range of 0.69 -0.88 and 0.45 -0.77 for calibration and 0.69 -0.79 and 0.34 -0.63 for validation respectively, and captured within a satisfactory uncertainty range of P-factor and R-factor values of 0.68 -0.93 and 0.73 -1.31 in 83%, 67%, 85.7% and 81.3% of the sub-watersheds based on multi-site simulation in spite of distinct watershed morphology although there are significant trade-offs in parameter sensitivity. Whilst green water is the dominant freshwater component across the basin relative to blue water, climate change may be a significant factor in changes in projected green water sustainability status, the combination of socioeconomic drivers and climate change may significantly impact the projected blue water sustainability status across the basin. Projected changes in green and blue water sustainability status have shown that more than 50% of the watershed will be ecologically fragile and identified freshwater geographic sustainability hotspots may be beyond restoration without adequate long-term river basin water resources plans.